Analysis Of Government Policy Towards Honorary Teachers - Muhammad Al Mighwar; Tariska Andini Nopaulita (Amandemen: Journal of Learning, Teaching and Educational Studies, 2023)
The purpose of this study is to describe and analyze the education policy of honorary teachers. The research tool used is descriptive qualitative method and data collection is in accordance with the research. Teachers are professionals who have the task of learning, educating and training. Educating means continuing and developing the values ​​of life. While teaching is developing science and technology. Honorary teachers are teachers who have the right to receive honorariums, both monthly and three months, honorary teachers also get legal protection and leave based on government regulations contained in the labor laws. Until now, honorary teachers still have not received proper welfare, because there are still problems experienced by honorary teachers